The Impact of Innovative Human Resource Practices on Employees Performance and Job Satisfaction: an Empirical study of Retail Industry of Odisha - Dhir, Sunpreet Kaur; Satpathy, Biswajit (International Journal of Psychosocial Rehabilitation, 2020)
Innovation is found to be the most imperative rootage for the economic development and organisational growth.. Today most of the organisations are facing problems like employee engagement and employee retention. To overcome this problem organisations’ need to innovate the human resource practices. These innovative human resources practice also enhances organisational effectiveness and also leads towards meliorate performance of the employees. The objective of the study is to find the impact of innovative human resource practices on Employees Performance and job satisfaction and to find out the most innovative human resource practices practiced in cement retail industry and clothing retail industry of odisha.